(untitled) (Italian Review of Legal History, 2024)
The paper aims at shedding some light on the life of Wilma Viscardini Donà, who was the first woman to be hired as adviser at the Legal Service of the European Commission, where she worked between the beginning of the Sixties and the beginning of the Seventies. The paper focuses on her time at the European Commission and the most important dossiers she worked on. Furthermore, it deals with her career as a lawyer litigating Community law cases.